A novel approach to the optimum design of MTMDs under seismic excitations - Fadel Miguel, Leandro Fleck; Lopez, Rafael Holdorf; Miguel, Letícia Fleck Fadel; Torii, André Jacomel (Structural control and health monitoring, 2016)
Summary This paper presents an efficient single‐stage scheme for the global optimization of multiple tuned mass dampers subjected to seismic excitations. To take into account the oscillators' vertical and horizontal distribution, the use of the ground structure concept is proposed. This procedure is very useful because it avoids the pre‐definition of the tuned mass dampers number and their placement. Because the multiple tuned mass dampers optimization problem is nonconvex and multimodal, this paper presents a novel hybrid stochastic/deterministic algorithm. The Firefly algorithm is used in the stochastic part, that is, to locate the global solution region and to provide a starting point to the local optimizer. The Nelder–Mead algorithm is then used as a local optimizer. Global search restarts are applied after convergence of the local search, allowing convergence to the global solution. In addition, because the structural response is obtained in the frequency domain, the scheme becomes very robust and requires considerably less computational effort than time history analysis. For illustration purposes, a numerical example on a ten‐story shear building is demonstrated. Copyright © 2016 John Wiley & Sons, Ltd.